Relation between biometric parameters and autumn-winter food availability in a roe deer (Capreolus capreolus) population in central Italy. Issue 1 (1st January 2020) - De Felice, E.; Mercati, F.; Pacioni, C.; Catorci, A.; Tardella, F. M.; Brusaferro, A.; Scocco, P.
Abstract: The numerical increase of roe deer has resulted in a noticeable growth of hunting activities allowing to have a great availability of biometrical data from both the hunted samples and the population by describing trends and variations and, then, optimize the consequent wildlife management decisions. Specifically, we analyzed biometric data of a roe deer ( Capreolus capreolus ) population at the Macerata Province, in central Italy. We focused on two animal groups: fawns (<11 months old) and adults (>2 years old). We assessed the relationship between body parameters and trophic resources available during the autumn-winter period. In particular, we analyzed live weight, head–trunk length, height at shoulders, chest circumference, length of hock, total length of the cranium, condilo-basal length, mastoid width, zygomatic width, ectorbital width, entorbital width, teeth row length and mandible length. In the context of studying trophic resources, we identified three environmental categories based on their carrying capacity and then assigned a specific environmental category to each sample. Statistical analysis was performed. In fawn, only zygomatic width showed significant differences both between sexes and among the environmental categories. In adult, the analysis showed significant differences between sexes for live weight, head–trunk length, length of hock and zygomatic width, with the highest values for males. Among environmental categories, the analysis showed significant differences for live weight, head–trunk length, length of hock chest circumference, length of hock, ectorbital width and teeth row length. This approach, applied to a broader database could be useful to identify suitable parameters to be used in planning the optimum selective hunting of roe deer.